If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-3+5X+4=7X+4
We move all terms to the left:
X-3+5X+4-(7X+4)=0
We add all the numbers together, and all the variables
6X-(7X+4)+1=0
We get rid of parentheses
6X-7X-4+1=0
We add all the numbers together, and all the variables
-1X-3=0
We move all terms containing X to the left, all other terms to the right
-X=3
X=3/-1
X=-3
| 12t−8t=−52 | | 9x+50+19x-50=180 | | 26a+264=580 | | 3r+1=-5 | | 10x+13=3(3x+3) | | 12+9q=16=8 | | 3/2(3/2+k)=39/8 | | 2x-3=-(4x+) | | 7/3x+1/3x=12+5/3x | | 1/4x-6=10 | | 6(x*x)-15x-50=0 | | -(8x+5)=-3x | | 147=-3+3(1-7v) | | 2x-5(x-5)=-4+5x-11 | | g-7/7=5/7 | | 2.50+3x=13 | | 10x+11=-5 | | -x+4=19+4x | | 8(x+2)-5(x-3)=16 | | 4(1-3n)-2n=-6n-20 | | 6x^-15x-50=0 | | x2-8=-2x | | 2a^2-24+13a=0 | | 18x+9=x^2+10x+25 | | 4-2(5-3n)=6+5n | | 17+3y-20=y | | 2a^2-24+13=0 | | 4k–3+5k=10k+6 | | 5x+9+5x-18=8x+9 | | -(5/8)y=-4 | | 3x=-2(x-7) | | 6/5+3/5x=57/20+7/4x+3/4 |